The Clinical Method and the Clinical Dilemmas. - Luis Alberto Corona Martinez; Mercedes Fonseca Hernández (Medisur)
The term ‘’clinic’’, among other meanings, refers to any information that suggests the presence of an illness and is obtained through questioning and physical examination processes that take place in the course of doctor-patient relationship. The purpose of this article is to summarize the challenges and dilemmas to be considered by students and young doctors in the patient's clinical approach, which completes the vision of the unquestionable positive role of clinical medical diagnosis. Different factors that can diminish the quality of obtained clinical information, thus interfering with the diagnostic process, have been classified into four groups: dependent on disease process, dependent on the individual patient or the source of information, dependent on the setting where information was obtained and dependent on the physician. As a generalization we state that the existence of the so-called challenges or dilemmas in clinical approach imply limitations to the clinical information obtained to be used with total reliability. Nevertheless, these dilemmas do not detract, nor even slightly, the values of clinical approach in the diagnostic process.